2008
DOI: 10.1021/om070244t
|View full text |Cite
|
Sign up to set email alerts
|

Pentadienyl Complexes of Alkali Metals: Structure and Bonding

Abstract: A systematic density functional study of the structure and bonding in the alkali-metal pentadienyl complexes C 5 H 7 E (E ) Li-Cs) and their analogues derived from the 2,4-dimethylpentadienyl ligand is performed. The bonding in these structures has been analyzed in some detail with reference to molecular orbital analysis, and energy partition analysis, obtained by density functional calculations. An energy decomposition analysis indicates that the electrostatic interaction is the main factor to be considered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…In this work, we analyzed the interaction of alkali metals( E + ) with [6]-and [14]helicene and the mobility of (E + )t herein. For the cases of complexes formed with [6]helicene, it was found that when the Li + is located above the center of each ring, the structure corresponds to an energy minimum, and an additional energy minimum structure arises when the Li + is placed at the middle of the helix.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we analyzed the interaction of alkali metals( E + ) with [6]-and [14]helicene and the mobility of (E + )t herein. For the cases of complexes formed with [6]helicene, it was found that when the Li + is located above the center of each ring, the structure corresponds to an energy minimum, and an additional energy minimum structure arises when the Li + is placed at the middle of the helix.…”
Section: Discussionmentioning
confidence: 99%
“…Note that for both cations, the complexes formed with [ 14]helicene have higher interaction energy with respectt ot heir [6]helicene counterparts, (7.5-9.0 kcal mol À1 higher for Li + ,a nd 4.5-5.5 kcal mol À1 higher for Cs + ,s ee Ta ble 4). Note that for both cations, the complexes formed with [ 14]helicene have higher interaction energy with respectt ot heir [6]helicene counterparts, (7.5-9.0 kcal mol À1 higher for Li + ,a nd 4.5-5.5 kcal mol À1 higher for Cs + ,s ee Ta ble 4).…”
Section: Cation Mobility In Longer Helicenesmentioning
confidence: 91%
See 2 more Smart Citations
“…A series of donor-acceptor heteroleptic open sandwiches with the formula CpM-M'Pyl (M = B, Al, Ga; M' = Li, Na; Cp = cyclopentadienyl; Pyl=pentadienyl) has been designed using density functional theory by Merino et al [35] in 2006. Cerpa et al [36] studied the structure and bonding in C 5 H 7 E (E=Li-Cs) and their analogues with density functional theory (DFT) calculations. In addition, the analogous metallocenes, such as CpM n Cp (M=Be, Mg, Ca, and Zn with n=2-5) [37], Fe(η 5 -E 5 ) 2 and FeCp(η 5 -E 5 ) (E=N, P, As, Sb) [38], [Ti(η 5 -E 5 ) 2 ] 2 − (E=CH, N, P, As, Sb) [39], Zn 2 (η 5 -Cp*) 2 [40], Cp−Zn− Cd−Cp [41], (η 5 -P 5 )-MM'(η 5 -P 5 ) and (η 5 -C 5 H 5 )MM'(η 5 -P 5 ) (M, M'=Zn, Cd) [42], were investigated.…”
Section: Introductionmentioning
confidence: 99%